PERLINDUNGAN HUKUM PERUSAHAAN TERKAIT PELANGGARAN RAHASIA DAGANG DALAM PERJANJIAN KERJA - Febrianti Anastasya Sarah Amelia; Irhamsah, Irhamsah; Felicitas Sri Marniati (Journal of Innovation Research and Knowledge, 2025)
A trade secret refers to information unknown to the public in the fields of technology and business that has economic value due to its usefulness in business activities and is kept confidential by the trade secret owner. In every company, employees perform tasks that expose them to the company’s trade secrets. Therefore, employment agreements are established. However, these trade secrets are sometimes disclosed by employees even after they leave the company. This research formulates the legal consequences of employment agreements between companies and employees concerning trade secret violations, as well as the legal protection available for companies as trade secret owners in the event of such violations. This research applies the legal protection theory by Satjipto Raharjo and the legal consequences theory by R. Soeroso. The research method used is normative juridical research, which involves legal literature studies or secondary data sources, including primary, secondary, and tertiary legal materials. The research approach includes statutory, analytical, conceptual, and case study approaches. Legal material collection techniques involve identifying and inventorying positive legal rules, book literature, journals, and other legal sources. Legal material analysis techniques involve grammatical and systematic legal interpretation, as well as analogy and legal refinement construction methods. The findings indicate that the legal consequences of employment agreements between companies and employees to protect trade secrets may restrict individuals' rights to choose, obtain, or change jobs, which conflicts with statutory regulations. The Indonesian Civil Code (KUHPerdata) has provisions regarding non-compete agreements in employment contracts. However, Indonesian law does not explicitly regulate limitations on the use of clauses that could harm employees in employment agreements. Employment agreements must meet the objective elements of an agreement, including clear limitations on competing companies, timeframes, and geographic scope. Legal protection for companies as trade secret owners in the event of employment termination ensures that trade secrets remain legally protected even after the employment agreement ends. This is because trade secrets are directly protected by law as long as the information remains confidential, has economic value, and is safeguarded. Preventive legal efforts by companies include establishing standard rules regarding trade secret protection, both during and after employment, since the Trade Secret Law ensures continuous protection as long as confidentiality is maintained.